Participatory governance in the context of local health councils: interviews with six local health council presidents in Northeastern Brazil - Jessica Scott Jerome
Abstract The aim of this study was to describe the challenges and opportunities faced by local health council presidents in their practice of participatory governance. In-depth interviews were conducted with six presidents at health posts at six neighborhoods located in a single region in a peripheral neighborhood in Fortaleza. The interviews were complemented by participant observation of local health council meetings conducted over a three-year period (2015-2017), and interviews with presidents of the municipal, regional and state health councils, as well as with more than twenty actors from government agencies and local associations. The data were analyzed with the help of Atlas.ti, and resulted in the identification of four core topics: the weakness of community representation, the generation of new health initiatives, the concern with the physical and material infrastructure of the councils, and the linkages between council Presidents and the historical network of community-based organizations (Associações Voluntárias) in the region in which the health posts were situated. The local health councils included in this study faced similar challenges to those documented by prior scholars, but also demonstrated the potential to cultivate local ideas for new health initiatives.